Contextual Cueing Effect Under Rapid Presentation - Xie, Xiaowei; Chen, Siyi; Zang, Xuelian (Frontiers in Psychology, 2020)
In contextual cueing, previously encountered context tends to facilitate the detection of the target embedded in it than when the target appears in a novel context. In this study, we investigated whether the contextual cueing could develop at early time when the search display was presented briefly. In four experiments, participants searched for a T target in an array of Ls. The results showed that with a rather short presentation time of the search display, participants were able to learn the spatial context and speeded up their response time overall, with the learning effect lasting for a long period. Specifically, the contextual cueing effect was observed either with or without a mask after a duration of 300-ms presentation of the search display. Such a context learning under rapid presentation could not operate only with the local context information repeated, thus suggesting that a global context was required to guide spatial attention when the viewing time of the search display was limited. Overall, these findings indicate that contextual cueing might arise at an ‘early’, target selection stage and that context learning under rapid presentation requires the associative learning between a global context and the target location.